Properties of concrete with eggshell powder: a review - Chong, Beng Wei; Rokiah, Othman; Putra Jaya, Ramadhansyah; Doh, Shu Ing; Xiaofeng, Li (Elsevier Ltd., 2020)
Sustainable concrete is currently a widely studied topic in order to reduce the environmental impact of cement. Substitute materials are usually industrial and municipal wastes. Eggshell powder as cement replacement is a viable option to produce green concrete. At the same time, it improves the disposal of eggshell, which is thrown away as household waste and mostly ends up in the landfill. This paper reviews the constituents, production techniques and properties of eggshell concrete (ESC). The paper presents the chemical compound of eggshell and the suitability of the waste as cement replacement. Tilis is followed by a discussion of the fresh, hardened and durability properties based on a variety of previous studies. At the optimal content of 10%, ESC has various advantages compared to conventional concrete. The advantages are associated with the high calcium content and good filling effect of eggshell powder. This includes improved hardened properties, reduced setting time, and increased resistance to water penetration and carbonation. Eggshell is also an accelerator to the hydration process. However, ESC shows weakness in chloride and sulphate environment due to the vulnerability of eggshell to these compounds. While studies on the material are available significantly, researches on durability properties of ESC should be enhanced.